Distribution of service reception and defense in men`s beach volleyball component tournaments of the Swatch FIVB World Tour - Seweryniak, T.; Mroczek, D.; Gryguc, P. (Journal of Physical Education and Sport, 2020)
This study attempts to assess the distribution of service reception and defense, which are understood as intentional directing of the ball into specific areas of the court. The authors determined the size, location, and shape of the optimal area to which the ball should be set after the team's first touch during service reception and defense. The basis of analysis wasthe men's beach volleyball matches of the Swatch FIVB World Tour 2012. The authors assume that there is a common optimal area for various beach volleyball teams to which the ball is directed during service reception and defense. The study sample consisted of 64 professional beach volleyball players from the top-level teams ranked by the International Volleyball Federation (FIVB). The players' actions were observed during 32 matches from three component tournaments of the Swatch FIVB World Tour 2012. Data were collected with a KINOVEA 0.8.15 motion tracking system. Visualizations of players' actions indifferent areas of the court were made. The observation and statistical analysis revealed that during service reception, the ball was most often directed into a 2 m × 4 m area (OA2) close to the net, near the center of the court. Thus, the court area OA2 is the optimal area to which the balls are most often set after service reception during top-level beach volleyball matches. In defensive play, the players also directed the ball close to the net and near the center of the court; however the optimal area for defense, unlike for service reception, cannot be delineated.